Wireless ambulatory ECG signal capture for HRV and cognitive load study using the NeuroMonitor platform - Sahadat, Md Nazmus; Consul-Pacareu, S.; Morshed, Bashir I. (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
The heart rhythms, controlled by the autonomic nervous system, can fluctuate with varying cognitive loads that can be captured with electrocardiogram (ECG) and heart rate variability (HRV) metrics. In this paper, we report customization of a wireless, ambulatory NeuroMonitor device originally developed for collecting electroencephalogram (EEG) signals as a platform for ECG and HRV data collection. The overall gain is altered to 93.86, while the band pass filter was set to 0.5 Hz to 126 Hz. The four independent inputs were connected to left arm, right arm, left leg and right leg. ECG signal and HRV data was collected during relax state and elevated cognitive load conditions. The signals were digitized at 256 sps and wirelessly transmitted to a remote computer for analysis. These cardiac signals were filtered and plotted using MATLAB. We demonstrate successful data collection that enables multiple applications of NeuroMonitor platform as an ambulatory physiological parameter monitoring hardware for long duration study of patients in natural settings.